SISTEM PEMASARAN NENAS DI KECAMATAN CIJERUK, KABUPATEN BOGOR - Murni Anggraeni; Suharno Suharno (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2016)
Bogor pineapple is the leading commodity ini Cijeruk subdisctrict, Bogor Regency, which is expected to increase the potential resource of local economy. The marketing of Bogor pineapple faces some constraints, such as (1) the large gap between farm price and retail price, (2) the weak bargaining position of farmers in the marketing chain, (3) the role of farmers group that have not been optimalized, (4) the farm location that is difficult to access, and (5) the competition with pineappples from outside Bogor. The purpose of this study was to determine the marketing channels formed in the marketing system of Bogor pineapple and the efficiency of each marketing channels so that we can provide the most efficient for pineapple farmers. The method of data collection is snowball sampling as many as 30 farmers to local traders, wholesalers, and retailers. Results of this research is that there are 10 marketing channel patterns formed. Seen from the value of marketing margin, farmer’s share, ratio of profit to cost, and the ease of access, the relatively efficient channelsare channel 3and 6. Both channels are the most selected marketing channels, which respectively amounted to 2,33 percent and 16,66 percent of farmers.